INTEGRATING STORYTELLING TECHNIQUES TO ENHANCE ENGLISH LANGUAGE SKILLS IN PRESCHOOL CHILDREN - Choriyeva Xurmo (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
ABSTRACT: This article examines the role of storytelling techniques in enhancing English language skills among preschool children. The study explores how narrative-based activities, including oral stories, picture books, and digital story apps, contribute to vocabulary development, listening comprehension, speaking, and creative expression. Emphasis is placed on age-appropriate design, interactive participation, and integrating play-based learning strategies with storytelling. The findings provide practical recommendations for educators to use storytelling effectively, fostering motivation, cognitive growth, and early foreign language proficiency in young learners.